Metal organic framework sodium ion battery positive electrode material Mn-PTO, and preparation method and application thereof
By using the three-dimensional crosslinked metal organic frame material Mn-PTO, which coordinates 2,7-dicarboxyl-4,5,9,10-pyrene tetraketone PTO-(COOH)2 and Mn2+, as the positive electrode material of sodium ion battery, the problems of low specific capacity and poor stability of existing materials are solved, and the improvement of high specific capacity and long cycle performance is achieved.
Patent Information
- Application Number
- CN202510132991.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-06
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2045-02-06
AI Technical Summary
The specific capacity of the existing sodium ion battery cathode material is low, and the long-cycle performance and stability are not good enough to meet market demand.
The three-dimensional crosslinked metal organic frame material Mn-PTO, which is coordinated with 2,7-dicarboxyl-4,5,9,10-pyrene tetraketone PTO-(COOH)2 and Mn2+, is used as the positive electrode material of sodium ion battery. The material is synthesized through a series of reactions, with four energy storage sites, providing high specific capacity, and forming a solid three-dimensional structure through hydrogen bonding, improving stability.
The Mn-PTO material reaches a high reversible specific capacity of 160.1 mAh g−1 under the current condition of 0.1 A g−1, and can still achieve an excellent reversible specific capacity of 118.1 mAh g−1 after 7000 cycles under the current condition of 5 A g−1, with better stability and rate performance than traditional materials.
Smart Images

Figure CN119570059A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a metal organic framework sodium ion battery positive electrode material Mn-PTO, a preparation method and an application thereof, and belongs to the technical field of battery development. Background Art
[0002] Lithium-ion batteries have occupied the main market of secondary batteries due to their high energy density and long cycle life. At present, most advanced energy storage systems use lithium-ion battery technology. Nevertheless, with the fluctuation of lithium-ion battery prices, especially the consumption of lithium resources and the shortage in the future, the development of lithium-ion batteries also has certain limitations. Therefore, sodium, which is abundant in resources, has attracted much attention. Sodium is in the same family as lithium and has similar electrochemical properties. Compared with lithium-ion batteries, sodium-ion batteries have many potential advantages such as low cost and good safety. They are suitable for large-scale energy storage and will surely become a new type of green and environmentally friendly energy storage battery with great development prospects.
[0003] In recent years, metal-organic frameworks (MOFs) with superior properties such as large specific surface area porous crystal structure, highly tunable composition and controllable functionality are considered to be electrode materials with more application prospects in sodium-ion batteries (SIBs).
[0004] The Chinese patent with publication number CN116102561A discloses a two-dimensional conductive metal organic framework material based on amino coordination tricyclic quinazoline. The material is used as the positive electrode of sodium ion battery in the voltage range of 1.0-3.6V and 1A g −1 At this current density, the discharge capacity after 1000 cycles is only 88 mAh g −1 The sodium battery cathode material described in this scheme has a low specific capacity, and its long cycle performance and stability at a higher current are not good enough to meet market demand. Summary of the invention
[0005] In order to solve the above-mentioned defects and shortcomings in the prior art, the present invention provides a preparation method and application of Mn-PTO, a positive electrode material for a metal organic framework sodium ion battery.
[0006] To solve the above technical problems: The first object of the present invention is to provide a metal organic framework sodium ion battery positive electrode material Mn-PTO, the positive electrode material is obtained by 2,7-dicarboxy-4,5,9,10-pyrenetetraketone PTO-(COOH)2 and Mn 2+A three-dimensional cross-linked metal organic framework formed by coordination. A three-dimensional metal organic framework was synthesized using the rigid carboxylic acid ligand 2,7-dicarboxy-4,5,9,10-pyrenetetraone (PTO-(COOH)2) and manganese acetate. Adjacent polymer chains are connected by hydrogen bonds to form a strong three-dimensional metal organic framework named Mn-PTO. When Mn-PTO is used as a sodium ion positive electrode, it exhibits excellent rate performance and long cycle performance, providing new ideas and solutions for the development of positive electrode materials for sodium ion batteries.
[0007] The second object of the present invention is to provide a method for preparing a metal organic framework sodium ion battery positive electrode material Mn-PTO, comprising the following steps: Step 1, synthesis of 2,7-dibromo-pyrene-4,5,9,10-tetraone (PTO-Br2): Pyrene-4,5,9,10-tetraone PTO, concentrated sulfuric acid and N-bromosuccinimide were added to a round-bottom flask, heated and stirred, and then cooled to room temperature; then slowly added dropwise to deionized water, vacuum filtered, collected precipitates, washed with deionized water, and the collected product was transferred to dimethyl sulfoxide (DMSO) for heating treatment, naturally cooled for recrystallization, and filtered; after repeating the recrystallization process (3 times), the filtrate was washed with dichloromethane and ether, and dried to obtain compound PTO-Br2; Step 2, synthesis of 2,7-dibromo-pyrene-4,5-,4,5-9,10-,9,10-tetra(1,4-dioxabutane) (PTO-Me-Br2): heat the compound PTO-Br2 obtained in step 1, ethylene glycol, p-toluenesulfonic acid monohydrate and toluene in a round-bottom flask under reflux, cool to room temperature, collect the precipitate by vacuum filtration, wash with deionized water and dry to obtain the compound PTO-Me-Br2; Step 3, synthesis of 2,7-dicyano-pyrene-4,5-,4,5-9,10-,9,10-tetra(1,4-dioxabutane) (PTO-Me-CN2): PTO-Me-Br2, cuprous cyanide and N-methylpyrrolidone were added to a three-necked flask, heated and stirred under an argon atmosphere, slowly cooled to room temperature, and ammonia water was added to obtain a crude product, which was washed with ammonia water and deionized water and dried to obtain PTO-Me-CN2; Step 4, synthesis of 2,7-dicarboxyl-pyrene-4,5-,4,5-9,10-,9,10-tetra(1,4-dioxabutane) (PTO-Me-(COOH)2): PTO-Me-CN2, 10% sodium hydroxide solution and ethanol were heated to reflux in a round-bottom flask, cooled to room temperature, acidified with hydrochloric acid, centrifuged to collect the precipitate, washed with deionized water, and dried to obtain PTO-Me-(COOH)2; Step 5. Synthesis of 2,7-dicarboxy-pyrene-4,5,9,10-tetraone (PTO-(COOH)2): PTO-Me-(COOH)2 and 60% perchloric acid were added to a round-bottom flask and stirred to mix. The precipitate was collected by centrifugation, washed with deionized water, and dried to obtain a yellow powder compound PTO-(COOH)2. Step 6. Synthesis of Mn-PTO: PTO-(COOH)2 is dissolved in DMSO and manganese acetate is dissolved in deionized water. Under stirring, the PTO-(COOH)2-DMSO solution is dropped into the manganese acetate aqueous solution; stirring and ultrasonic treatment are performed at room temperature; then the mixture is transferred to a high-pressure reactor, cooled naturally, and then centrifuged to obtain a precipitate, which is washed with DMSO, anhydrous ethanol and deionized water in turn, and dried to obtain the product Mn-PTO.
[0008] Furthermore, the reaction temperature of the high-pressure reactor is 120° C.-200° C., and the reaction time is 40-100 hours.
[0009] Furthermore, the reaction temperature of the autoclave was 160° C., and the reaction time was 72 hours.
[0010] Furthermore, the stirring speed at room temperature was 500 rpm and the stirring time was 4 hours.
[0011] Furthermore, the ultrasonication time was 30 minutes.
[0012] The third object of the present invention is to provide an application of the positive electrode material Mn-PTO prepared by the above-mentioned preparation method in the preparation of a sodium ion battery.
[0013] Furthermore, the positive electrode material Mn-PTO is mixed with conductive carbon black and polyvinylidene fluoride and ground, and N-methylpyrrolidone is added as a solvent to stir the slurry for 8-12 hours. The slurry is coated on a carbon-coated aluminum foil after ultrasonic treatment, and then cut into pieces after drying in a vacuum oven.
[0014] Furthermore, the mass ratio of the positive electrode material Mn-PTO to the conductive carbon black and polyvinylidene fluoride is 6:3:1.
[0015] Furthermore, the negative electrode material is a sodium metal pressed sheet, and the electrolyte is NaPF6 dissolved in 1,3-epoxypentane / ethylene glycol dimethyl ether.
[0016] Beneficial technical effects achieved by the present invention: The present application provides a metal organic framework sodium ion battery positive electrode material Mn-PTO, a preparation method and an application thereof, selects an organic ligand pyrene tetraketone with conjugated extension, and synthesizes 2,7-dicarboxyl-4,5,9,10-pyrene tetraketone PTO-(COOH)2 through a series of reactions, which has four energy storage sites and can provide a high specific capacity. Since the material has a unique cross-linked three-dimensional structure, it can be used as a positive electrode material for SIBs. Through electrical performance tests, it can be seen that the sodium ion battery made of the material as a positive electrode material has a high specific capacity of 0.1 A g −1 The current reached 160.1 mAh g −1 This may be because the moderate interlayer distance (2.06 Å) has strong π-π stacking, which can form a continuous ion transport channel, reduce the ion migration resistance, and facilitate Na + The deintercalation and insertion of the nanostructured carbon nanotubes have good stability, thereby improving the rate performance; even at 5 A g −1 Under current conditions, 118.1 mAh g can be achieved after 7000 cycles. −1 In addition, at 10 A g −1 The high current can be cycled stably for 10,000 times, and the specific capacity is still 83.5 mAh g −1 Therefore, the positive electrode material Mn-PTO has great potential in the field of sodium ion battery positive electrode. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 The infrared spectrum and yield statistics of each intermediate in the preparation process of the embodiments of the present invention; Figure 2 The NMR of each intermediate in the preparation process of the present invention is 1 H spectrum and 13 C spectrum; Figure 3 The infrared spectra of the products obtained from different solvents in the synthesis steps of Mn-PTO in the embodiment of the present invention; Figure 4 The X-ray diffraction spectra of the products obtained from different solvents in the synthesis steps of Mn-PTO in the embodiment of the present invention; Figure 5 Infrared spectra of products obtained at different reaction temperatures in the synthesis steps of Mn-PTO in the embodiment of the present invention; Figure 6 The X-ray diffraction spectra of the products obtained at different reaction temperatures in the synthesis steps of Mn-PTO in the embodiment of the present invention; Figure 7 X-ray diffraction spectrum of the Mn-PTO product obtained by the preparation method of the embodiment of the present invention; Figure 8 Infrared spectrum of the Mn-PTO product obtained by the preparation method of the embodiment of the present invention; Fig. 9 Raman spectrum of the Mn-PTO product obtained by the preparation method of the embodiment of the present invention; Fig.10 A schematic structural diagram of a Mn-PTO product obtained by the preparation method of an embodiment of the present invention; Fig.11 Schematic diagram of the three-dimensional structure of the Mn-PTO product obtained by the preparation method of the embodiment of the present invention; Fig.12 The present invention is a scanning electron microscope image of the Mn-PTO product obtained by the preparation method of the embodiment; Fig.13 The present invention is an elemental mapping diagram of the Mn-PTO product obtained by the preparation method of the embodiment; Fig.14 The Mn-PTO product obtained by the preparation method of the present invention has a −1 Cycling performance diagram under current density; Fig.15 The preparation method of the present invention is pure DMSO solvent, and the Mn-PTO product obtained is 0.2 A g −1 Cycling performance diagram under current density; Fig.16 Rate performance diagram of the Mn-PTO product obtained by the preparation method of the embodiment of the present invention; Fig.17 The Mn-PTO product obtained by the preparation method of the present invention has a −1 Long cycle diagram under high current; Fig.18 The Mn-PTO product obtained by the preparation method of the present invention has a −1 Long cycle diagram under high current. DETAILED DESCRIPTION
[0018] The present invention will be further described below in conjunction with specific examples. The following examples are only used to more clearly illustrate the technical solutions of the present invention, and are not intended to limit the scope of protection of the present invention.
[0019] The present invention is further described below in conjunction with the accompanying drawings and embodiments.
[0020] The present invention provides a metal organic framework sodium ion battery positive electrode material Mn-PTO, the positive electrode material is prepared by 2,7-dicarboxyl-4,5,9,10-pyrenetetraketone PTO-(COOH)2 and Mn 2+A three-dimensional cross-linked metal organic framework was formed by coordination. A three-dimensional metal organic framework was synthesized using a rigid carboxylic acid ligand 2,7-dicarboxy-4,5,9,10-pyrenetetraone (PTO-(COOH)2) and manganese acetate. Adjacent polymer chains are connected by hydrogen bonds, thus forming a strong three-dimensional metal organic framework named Mn-PTO. Its structural diagram is shown in Fig.10 and Fig.11 As shown: it is composed of a one-dimensional coordination polymer chain and a triple hydrogen bond. Three O-H···O hydrogen bonds are formed between C=O, COOH, and H2O, with lengths of 1.88 Å, 1.94 Å, and 2.04 Å. The one-dimensional chain is connected with hydrogen bonds to form a cross-linked three-dimensional structure, which makes the material highly stable; the three-dimensional cross-linked structure allows the interlayer spacing of parallel layers to be 2.06 Å, indicating that the material has strong π-π stacking, which is conducive to the formation of continuous ion transport channels; the angle of overlap between layers is 71.228°, and the cross-linked three-dimensional structure is conducive to the exposure of active sites and improves the utilization of active sites. When Mn-PTO is used as a sodium ion positive electrode, it exhibits excellent rate performance and long cycle performance, providing new ideas and solutions for the development of positive electrode materials for sodium ion batteries. Table 1 is a crystallographic data table of Mn-PTO.
[0021] Table 1
[0022] It can be seen from Table 1 that Mn-PTO belongs to the monoclinic system. P 1 2 1 / c 1 Space group, lattice parameters are a = 13.8122 Å, b = 10.8118 Å, c = 5.5750 Å, α = γ = 90°, β = 96.910°.
[0023] Example 1 Preparation of Metal-Organic Framework Sodium Ion Battery Cathode Material Mn-PTO 1) Synthesis of 2,7-dibromo-pyrene-4,5,9,10-tetraone (PTO-Br2): Pyrene-4,5,9,10-tetraone (PTO) (1200 mg, 4.58 mol), concentrated sulfuric acid (30 mL) and N-bromosuccinimide (1800 mg, 10.11 mol) were added to a 500 mL round-bottom flask. The mixture was stirred at 45°C for 2 hours and then cooled to room temperature. The mixture was slowly added dropwise to 400 mL of 0°C deionized water. The precipitate was collected by vacuum filtration and washed with deionized water. The collected product was heated at 130°C for 3 hours in 100 mL of dimethyl sulfoxide (DMSO) and then naturally cooled to recrystallize. The product was filtered to obtain the product. After recrystallization three times, the filtrate was washed with dichloromethane and ether. The product was dried at 80°C to obtain the target compound (1500.2 mg, 3.59 mol, 125%).
[0024] 2) Synthesis of 2,7-dibromo-pyrene-4,5-,4,5-9,10-,9,10-tetra(1,4-dioxabutane) (PTO-Me-Br2) (-Me represents -CH3): PTO-Br2 (1500.4 mg, 3.59 mol), ethylene glycol (36 mL), p-toluenesulfonic acid monohydrate (1364.2 mg, 7.18 mol) and toluene (36 mL) were added to a 500 mL round-bottom flask. The mixture was stirred at 120 °C for 24 hours and then cooled to room temperature. The precipitate was collected by vacuum filtration, washed with deionized water, and dried at 80 °C to obtain the target compound (1678.2 mg, 2.82 mol, 112%).
[0025] 3) Synthesis of 2,7-dicyano-pyrene-4,5-,4,5-9,10-,9,10-tetra(1,4-dioxabutane) (PTO-Me-CN2): PTO-Me-Br2 (1678.2 mg, 2.82 mol), cuprous cyanide (2328.2 mg, 26.0 mol) and N-methylpyrrolidone (56 mL) were added to a 500 mL three-necked flask. The mixture was heated and stirred at 190 °C for 12 hours under an argon atmosphere and then slowly cooled to room temperature. 200 mL of ammonia water was added to remove the remaining Cu + The crude product obtained after centrifugation was washed with ammonia water and deionized water. The collected product was dried at 80 °C to obtain the target compound (1214.0 mg, 2.49 mol, 72%).
[0026] 4) Synthesis of 2,7-dicarboxy-pyrene-4,5-,4,5-9,10-,9,10-tetra(1,4-dioxabutane) (PTO-Me-(COOH)2): PTO-Me-CN2 (1214.0 mg, 2.49 mol), 10% sodium hydroxide solution (30 mL) and ethanol (60 mL) were added to a 500 mL round-bottom flask. The mixture was stirred at 80°C for 4 hours, cooled to room temperature, and acidified with 1 M hydrochloric acid (80 mL). The precipitate was collected by centrifugation, washed with deionized water, and dried at 80°C to obtain the target compound (1137.5 mg, 2.16 mmol, 94%).
[0027] 5) Synthesis of 2,7-carboxy-pyrene-4,5,9,10-tetraone (PTO-(COOH)2): PTO-Me-(COOH)2 (1137.5 mg, 2.16 mol) and 60% perchloric acid (95 mL) were added to a 500 mL round-bottom flask. The mixture was stirred at 0°C for 12 hours. The precipitate was collected by centrifugation, washed with deionized water, and dried at 80°C to obtain the target compound (731.1 mg, 1.81 mol, 64%) as a yellow powder.
[0028] 6) Synthesis of Mn-PTO: The prepared PTO-(COOH)2 (105 mg, 0.3 mmol) was dissolved in 45 mL DMSO, and manganese acetate (98 mg, 0.3 mmol) was dissolved in 45 mL deionized water. The PTO-(COOH)2-DMSO solution was dropped into the manganese acetate aqueous solution under stirring. The reaction was stirred at 500 rpm for 4 hours at room temperature and ultrasonicated for 30 minutes. Then, it was transferred to an autoclave and heated at 160°C for 72 hours. The precipitate was separated by centrifugation. The powder was then washed with DMSO (50 mL × 2), anhydrous ethanol (50 mL × 2) and deionized water (50 mL × 2), and dried at 80°C. Yield: 85.1 mg (81%, based on PTO-(COOH)2).
[0029] During the preparation process, the intermediates in each step were characterized and the yield was statistically analyzed. Figure 1 and Figure 2 As shown. Figure 1 This is the infrared spectrum and yield statistics of each intermediate in the preparation process. It can be seen from the figure that the changes in the characteristic groups indicate that the synthesis is successful. Figure 2 The NMR of each intermediate in the preparation process 1 H spectrum and 13 The X-ray diffraction spectrum, infrared spectrum and Raman spectrum of the product Mn-PTO obtained by the above preparation method are respectively as follows: Figure 7-Figure 9 As shown. Figure 7 It can be seen that the Mn-PTO product obtained by the above method exhibits high crystallinity, and the peak shape and peak position of Mn-PTO are consistent with the single crystal simulation peak, proving that the material is pure phase. Figure 8 The disappearance of the OH characteristic peak proves the success of the coordination. Meanwhile, the peak of Mn-PTO at 3600-3200 cm −1 Three hydrogen bond characteristic peaks appeared, corresponding to three types of intermolecular hydrogen bonds. Fig. 9 It can be seen that the Mn-PTO product is at 650 cm −1 A Mn-O peak appeared at , further proving the success of the coordination. Fig.12 This is a scanning electron microscope image of the Mn-PTO product. It can be seen from the image that it is a three-dimensional cross-linked fiber rod structure. Fig.13 This is the element mapping diagram of the Mn-PTO product. It can be seen that the C, O, and Mn elements are evenly distributed.
[0030] Example 2 Effect of the reaction temperature of the autoclave on the product in the synthesis step of Mn-PTO The preparation process was the same as in Example 1, and the reaction temperatures of the autoclave were 120°C, 140°C, 160°C, 180°C, and 200°C, respectively. The product was characterized by infrared spectroscopy and X-ray diffraction spectroscopy. Figure 5 and Figure 6 As shown. Figure 5 It can be seen that the Mn-PTO reacted at 120℃, 140℃, 160℃, 180℃, and 200℃ has a peak at 2574 cm in the infrared spectrum. −1 The disappearance of the OH characteristic peak at , indicates the success of Mn coordination. The hydrogen bond peak is most obvious in the sample synthesized at 160℃, indicating that the hydrogen bond generated by the sample synthesized at 160℃ is the most stable. Figure 6 It can be seen that the X-ray peaks in the sample synthesized at 160℃ are the most numerous and the peak shape is the sharpest, indicating that the sample synthesized at 160℃ has the best crystallinity.
[0031] Example 3: Assembly of the battery The Mn-PTO prepared in Example 1 was ground with conductive carbon black and polyvinylidene fluoride in a mass ratio of 6:3:1, and N-methylpyrrolidone was added as a solvent to stir the slurry. The slurry was stirred for 8 hours. The slurry was coated on a carbon-coated aluminum foil after ultrasound, and cut into pieces after drying in a vacuum oven at 80°C. The diameter of the pole piece was 10 mm, and the battery assembly used a CR2032 battery shell, the negative electrode used a sodium metal press, and the electrolyte used 0.5 M NaPF6 dissolved in 1,3-epoxypentane / ethylene glycol dimethyl ether (v:v = 1:1). The assembled battery was tested and the results were as follows: Fig.14 0.2 A g −1Cycling performance under current density: After 500 cycles, the specific capacity has almost no decay and is still 155 mAh g −1 The specific capacity of PTO-(COOH)2 decreased from 117.1 mAh g to 1.3 mAh g after 500 cycles. −1 Down to 81.2 mAhg −1 , the specific capacity retention rate is relatively low, only 69.4%.
[0032] Fig.16 The rate performance diagram is: 0.2, 0.5, 1, 2, 5, 10, 20 A g −1 At the current densities, the discharge capacities of Mn-PTO are 152.9, 149.5, 146.4, 142.6, 133.4, 127.3, and 124.1 mAh g −1 Its rate performance is better than most reported MOFs cathodes. Moreover, the specific capacity of Mn-PTO can reach 0.2 A g −1 The discharge capacities of PTO-(COOH)2 were 113.0, 101.5, 96.6, 91.9, 85.4, 80.1, and 74.8 mAh g, respectively. −1 As the current density increases from 0.2 A g −1 Increase to 20 A g −1 The specific capacity has obviously decayed and cannot be restored to 0.2 A g −1 The initial value when .
[0033] Fig.17 At 5 A g −1 Long cycle diagram under high current: at 5 A g −1 After 7000 cycles at a current of −1 The discharge capacity retention rate of PTO-(COOH)2 was 86.8%. −1 The discharge capacity under the condition was maintained at 62.4 mAh g after 3000 cycles. −1 (Specific capacity retention rate is 65.8%).
[0034] Fig.18 10 A g −1 Long cycle diagram under high current: After 10,000 cycles, the specific capacity of the Mn-PTO positive electrode increased from 127.1 mAh g−1 Down to 83.5 mAh g −1 The specific capacity retention rate is 65.4%, which is equivalent to a specific capacity decay of only 0.00346% per cycle. −1 The specific capacity under the condition increased from 88.0 mAh g −1 Down to 31.5 mAh g −1 (Specific capacity retention rate is 35.8%). This further proves the excellent cycling stability of Mn-PTO.
[0035] Example 4 Effect of solvent on product in the synthesis step of Mn-PTO The preparation process was the same as in Example 1, except that the prepared PTO-(COOH)2 (105 mg, 0.3 mmol) was dissolved in 45 mL DMSO, and manganese acetate (98 mg, 0.3 mmol) was dissolved in 45 mL DMSO. The obtained Mn-PTO organic metal framework was characterized by infrared spectroscopy and X-ray diffraction spectroscopy. The results are as follows: Figure 3 and Figure 4 As shown. Figure 3 It can be seen that 2574cm −1 The OH characteristic peak at 3600 cm −1 Three O−H···O hydrogen bond characteristic peaks appeared at ; Figure 4 The X-ray diffraction spectrum of Mn-PTO synthesized using different solvents shows that the X-ray diffraction spectrum of Mn-PTO synthesized using a mixed solvent of (DMSO+H2O) has obvious peaks, sharp peaks, and high intensity, indicating that the crystallinity is very high; while the X-ray diffraction spectrum of Mn-PTO synthesized using pure DMSO has only one broad diffraction peak, indicating that the material has almost no crystallinity.
[0036] The product was then assembled into a battery in the manner of Example 3, which was −1 The cycling performance at current density is Fig.15 As shown: Mn-DMSO-PTO has a disordered structure, large fluctuations in coulombic efficiency, unstable specific capacity, and rapidly decays after 100 cycles.
[0037] The present invention has been disclosed above with preferred embodiments, but they are not intended to limit the present invention. Any technical solutions obtained by adopting equivalent replacement or equivalent transformation solutions fall within the protection scope of the present invention.
Claims
1. A metal organic framework sodium ion battery cathode material Mn-PTO, characterized in that: The positive electrode material is prepared by 2,7-dicarboxyl-4,5,9,10-pyrenetetraone PTO-(COOH)2 and Mn 2+ Coordination-formed three-dimensional cross-linked metal-organic frameworks.
2. A method for preparing a metal organic framework sodium ion battery positive electrode material Mn-PTO, characterized in that The following steps are involved: Step 1, synthesis of 2,7-dibromo-pyrene-4,5,9,10-tetraone (PTO-Br2): Pyrene-4,5,9,10-tetraone PTO, concentrated sulfuric acid and N-bromosuccinimide are added to a round-bottom flask, heated and stirred to mix, and then cooled to room temperature; then slowly added dropwise to deionized water, vacuum filtered, collected precipitates, washed with deionized water, and the collected product was transferred to dimethyl sulfoxide (DMSO) for heating treatment, naturally cooled for recrystallization, and filtered; after repeating the recrystallization process, the filtrate was washed with dichloromethane and ether, and dried to obtain compound PTO-Br2; Step 2, synthesis of 2,7-dibromo-pyrene-4,5-,4,5-9,10-,9,10-tetra(1,4-dioxabutane) (PTO-Me-Br2): heat the compound PTO-Br2 obtained in step 1, ethylene glycol, p-toluenesulfonic acid monohydrate and toluene in a round-bottom flask under reflux, cool to room temperature, collect the precipitate by vacuum filtration, wash with deionized water and dry to obtain the compound PTO-Me-Br2; Step 3, synthesis of 2,7-dicyano-pyrene-4,5-,4,5-9,10-,9,10-tetra(1,4-dioxabutane) (PTO-Me-CN2): PTO-Me-Br2, cuprous cyanide and N-methylpyrrolidone were added to a three-necked flask, heated and stirred under an argon atmosphere, slowly cooled to room temperature, and ammonia water was added to obtain a crude product, which was washed with ammonia water and deionized water and dried to obtain PTO-Me-CN2; Step 4, synthesis of 2,7-dicarboxyl-pyrene-4,5-,4,5-9,10-,9,10-tetra(1,4-dioxabutane) (PTO-Me-(COOH)2): PTO-Me-CN2, 10% sodium hydroxide solution and ethanol were heated to reflux in a round-bottom flask, cooled to room temperature, acidified with hydrochloric acid, centrifuged to collect the precipitate, washed with deionized water, and dried to obtain PTO-Me-(COOH)2; Step 5, synthesis of 2,7-carboxy-pyrene-4,5,9,10-tetraone (PTO-(COOH)2): PTO-Me-(COOH)2 and 60% perchloric acid were added to a round-bottom flask and stirred to mix, and the precipitate was collected by centrifugation, washed with deionized water, and dried to obtain a yellow powder compound PTO-(COOH)2; Step 6. Synthesis of Mn-PTO: PTO-(COOH)2 is dissolved in DMSO and manganese acetate is dissolved in deionized water. Under stirring, the PTO-(COOH)2-DMSO solution is dropped into the manganese acetate aqueous solution; stirring and ultrasonic treatment are performed at room temperature; then the mixture is transferred to a high-pressure reactor, cooled naturally and centrifuged to obtain a precipitate, which is washed with DMSO, anhydrous ethanol and deionized water in turn, and dried to obtain the product Mn-PTO.
3. The method for preparing the metal organic framework sodium ion battery positive electrode material Mn-PTO according to claim 2, characterized in that: In step six, the reaction temperature of the high-pressure reactor is 120° C.-200° C., and the reaction time is 40-100 hours.
4. The method for preparing the metal organic framework sodium ion battery positive electrode material Mn-PTO according to claim 3, characterized in that: The reaction temperature of the autoclave was 160° C. and the reaction time was 72 hours.
5. The method for preparing the metal organic framework sodium ion battery positive electrode material Mn-PTO according to claim 3, characterized in that: The stirring speed was 500 rpm at room temperature and the stirring time was 4 hours.
6. The method for preparing the metal organic framework sodium ion battery positive electrode material Mn-PTO according to claim 3, characterized in that: The ultrasonication time was 30 minutes.
7. Use of the metal organic framework sodium ion battery positive electrode material Mn-PTO according to claim 1, or the metal organic framework sodium ion battery positive electrode material Mn-PTO prepared by the preparation method according to claim 2 in the preparation of sodium ion batteries.
8. The use according to claim 7, characterized in that: The positive electrode material Mn-PTO is mixed with conductive carbon black and polyvinylidene fluoride and ground, and N-methylpyrrolidone is added as a solvent to stir the slurry for 8-12 hours. The slurry is coated on a carbon-coated aluminum foil after ultrasonic treatment, and then cut into pieces after drying in a vacuum oven.
9. The use according to claim 8, characterized in that: The mass ratio of the positive electrode material Mn-PTO to the conductive carbon black and polyvinylidene fluoride is 6:3:
1.
10. The use according to claim 7, characterized in that: The negative electrode material is sodium metal pressed tablets, and the electrolyte is NaPF6 dissolved in 1,3-epoxypentane / ethylene glycol dimethyl ether.
Citation Information
Patent Citations
Polymer containing pyrazine-benzoquinone structure and application of polymer in lithium ion / aqueous zinc ion battery
CN114920930A
Triazine covalent organic framework material based on pyrene tetraketone as well as preparation method and application of triazine covalent organic framework material
CN115850697A
Electrode active material for power storage device and power storage device
JP2014175211A
Porous coordination polymer, gas adsorbent, hydrogen adsorbent, and hydrogen storage tank
JP2020196668A
Indium zinc-based alloy anodes forming porous structure for aqueous zinc batteries
US20230282816A1
Cited By
Composite modified lithium-rich manganese-based positive electrode material as well as preparation method and application thereof
CN120527386A